Arms Trade As Instrument Of Insecurity In Nigeria - Tella, Charas Madu; Abdulhakeem, Adejumo; Hassan, Muritala Babatunde (Advances in Social Sciences Research Journal, 2018)
Nigeria in recent years has witnessed continued escalation of acts of insecurity. Insurgency, civil violence, kidnapping, militancy, ethnic/religious clashes, allegedly to have been caused by injustice, intolerance, poverty, unemployment, extremism, corruption, ill education and poor governance, have been on the increase in the country. This is not unconnected with the prevalence issue of illegal arms trade and proliferation of small arms and light weapons in the country. Arms are regarded as small weapons that are harmful and dangerous to human existence, they include revolvers, pistol, riffles, sub-machine guns, mounted grenade launchers, while the light weapon refers to heavy machine guns, hand held under-barred portable anti-aircraft missile system. It is on this premise that this study examines the relationship between the spate of insecurity in Nigeria and arms trade. In doing this, the authors used primary and secondary sources of data using chi-square techniques to analyze the data. A total of 300 questionnaires were produced, distributed, retrieved and analyzed. The findings revealed, among other things, that terrorism, conflicts and violence have posed serious threat to national development. As such, it was recommended that government should take a decisive action to prosecute any person found in possession of any arms, irrespective of political affiliation.